India's new Israel policy : how the decline of the Palestinian issue and economic reorientation accelerate Indo-Israeli cooperation - Kumaraswamy, P. R. (2019)
Zusammenfassung: In January 2019, about two weeks before India’s Republic Day, Israel’s National Security Advisor, Meir Ben-Shabbat, flew to New Delhi and met Prime Minister (PM) Narendra Modi. While such consultations have been routine for the past two decades, the Israeli official chose the direct Air India flight from Tel Aviv – a new flight connection that could only be established due to an unprecedented permit for Israel-bound flights to fly over Saudi airspace. The small incident highlights the distance that India and Israel have traveled since the normalization of diplomatic relations in 1992. Today, the two states share an ever-growing cooperation, especially in the areas of security and economic development. This rapprochement with Israel is embedded in India’s broader Middle East strategy, in which especially the Gulf Arab states are important partners. Thus, India-Israel relations have also been catalyzed by the improvement in ties between Israel and the Gulf States as well as the diminishing role played by the Palestinian issue. This, in turn, has led India, especially under Modi, not only to strengthen its ties with Israel, but also to de-hyphenate those ties from the Israeli-Palestinian conflict, leading to a marginalization of the Palestinian question in Indian foreign policy